Physical exercise has control over players’ emotions and psychological capital: A moderating role of coach behavior - Dr. Muhammad Awais Bhatti; Dr. Abdulrahman Abdullah Alsughayir (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This is quantitative research employing a cross-sectional research design for data collection. This study's theoretical approach is intended to evaluate the impact of physical exercise on players' emotions and psychological empowerment in Saudi Arabia, with the coach's behavior as a moderator. There are no substantial reasons for this link presented by the studies in the literature. The players with destructive emotions and low psychological empowerment are unsuitable for the team because they hinder its performance. Empowering the players psychologically is essential for team performance. According to the research, athletes' emotions and psychological empowerment improve when they engage in appropriate exercise under the guidance of a committed coach. The research revealed practical consequences that are important for managing various teams to strengthen the players' psychological empowerment and improve their moods. This research improves the theoretical understanding of player emotions and psychological empowerment by introducing two direct linkages and two moderating relationships. The future recommendations of this study are endorsed for researchers contemplating work in the field of psychic empowerment and psychological control of players.